Effect of EDTA with various surface active agents on the bond strength of an epoxy resin-based sealer to dentin: ex vivo - Mehmet Burak Güneşer; Seyit Bilal Özdemir; Dilara Arslan; Asiye Nur Dinçer (Gazi University, 2017)
Objective: The aim of this in vitro study was to evaluate the effect of addition of various surface-modifying agents to EDTA solution on the bond strength of an epoxy-based sealer to the root canal dentin. Materials and Method: Sixty single-rooted human mandibular premolars were decoronated and instrumented using rotary system. The specimens were then randomly divided into four groups (n=15) according to irrigation with different EDTA solution (Wizard, Rehber Kimya, Istanbul, Turkey) combinations as follows: Group 1: 17% EDTA + 0.1% benzalkonium chloride; Group 2: 17% EDTA + 0.1% Tween 80; Group 3: 17% EDTA + 0.1% Triton X-100 and control group: 17% EDTA without any surface-modifying agents. Surface tensions of the EDTA solutions were controlled with a tensiometer. Final irrigation was with 5 mL of 5% sodium hypochlorite (Wizard) for 1 min, followed by 5 mL of the mentioned EDTA solution for another minute. Roots were obturated with gutta-percha and AH Plus sealer (Dentsply DeTrey, Konstanz, Germany) using cold lateral compaction technique. Horizontal root sections were obtained, and push-out test was used to measure the bond strength between the root canal dentin and sealer. Data were analyzed using the two-way analysis of variance and post hoc Tukey tests (p<0.05). Results: The bond strength of sealer in groups irrigated with EDTA in combination with surface modifying agents did not differ from that of the control (p=0.106). The coronal and middle third in all groups exhibited significantly greater bond strength values when compared with the apical third (p=0.004 and p=0.002, respectively). There was no statistical significant difference between the coronal and the middle thirds (p=0.979). Conclusion: The addition of surface modifying agents to EDTA solution did not affect the bond strength of the epoxy resin-based sealer.